Automating curriculum management tasks (Master of Software Engineering, unofficial) - Vijayakumar, Rajarajan (My University, 2006)
This manuscript describes a web based tool that assists in automating curriculum proposal and change procedures, curricular data maintenance and course catalog publication at the University of Wisconsin-La Crosse. Curriculum proposals are initiated by departments, approved by curriculum committees and finally maintained by Records and Registrations department. The current manual system is paper intensive, inconsistent, confusing and follows a manual workflow. The tool provides the following features: 1.) Using this tool, a faculty member will be able to create new course and program proposals through a web based application. 2.) The current database (namely catalog master) consists of unnormalized tables and consists of neither constraints nor relationships; so a new database has been developed to tackle the problem of redundancy and inconsistency 3.) The tool allows the creation of several reports. This manuscript describes the development of the curriculum management tool; in particular, it describes the activities performed in each phase, the challenges encountered, the issues that arose, the current status of the project, and its limitations and continuing work.
Keywords: Curriculum planning -- Wisconsin -- La Crosse; Education -- Curricula -- Computer programs